PS-077 Assessment of the medication system in an university hospital: risk mapping with a priori and a posteriori approaches. (24th February 2014) - Bigot, A; Promis, A; Irazusta, O; Cazal, J; Delenclos, L; Le Floch Meunier, B; Cestac, P; Massip, P
Abstract : Background: Different aspects of the medicines system (MS) must be made safe, which involves several health care professionals. Purpose: To classify risks and plan corrective actions using results obtained with a priori and a posteriori methods. Materials and methods: To identify risks with an a priori method, we conducted risk mapping with a multidisciplinary risk management tool called "Inter Diag Medicaments". Risk mapping was conducted in 25 randomly selected wards from January to September 2013 with doctors, nurses, pharmacists and a quality engineer. About an a posteriori method, we collected adverse MS events reported by units on dedicated software. A thorough and systematic analysis was performed with the professionals involved to identify chronology, causes (patient, professionals, management, process, etc.) and to estimate the severity of the adverse event. For each method, we classified and confronted the failing items in order to plan improvements and monitoring. Results: In 2013, 45 adverse MS events were reported. Concerning the item "safety policy in the units", risk mapping showed a lack of feedback of experience and insufficient knowledge of protocols. Of these 45 reports, 22 medicines errors were related to this safety policy, and of these 7 concerned lack of feedback and 10 insufficient knowledge of protocols. About "making safe the process of prescription, dispensing, preparation and administration", the a priori method evidenced poor risk control regarding prescriptions and dispensing for named patients with respectively 4 and 8 reports. Finally, 6 reports concerned preparation and administration. Risks with these were not identified by the a priori approach. Conclusions: Risk mapping does not identify all risks, particularly for the preparation and administration process. These results illustrate that the combination of these methods improves completeness of the mapping and enables us to plan priority corrective actions. This method will be continued in other units and extended to the medical devices system. No conflict of interest.